Reduction of venous pressure during the resection of liver metastases compromises enteric blood flow: IGFBP-1 as a novel biomarker of intestinal barrier injury - Hermes Vieira Barbeiro (Clinics)
OBJECTIVES: Disruption of the intestinal barrier and bacterial translocation commonly occur when intestinal blood flow is compromised. The aim of this study was to determine whether liver resection induces intestinal damage. METHODS: We investigated intestinal fatty-acid binding protein and insulin-like growth factor binding protein levels in the plasma of patients who underwent liver resection. RESULTS: We show that liver resection is associated with significant intestinal barrier injury, even if the Pringle maneuver is not performed. CONCLUSION: We propose the use of insulin-like growth factor binding protein-1 as a novel biomarker of intestinal damage in such situations.